Planning, implementation, and sustaining high coverage of human papillomavirus (HPV) vaccination programs: What works in the context of low-resource countries? - Waheed, Dur-E-Nayab; Bolio, Ana; Guillaume, Dominique; Sidibe, Anissa; Morgan, Christopher; Karafillakis, Emilie; Holloway, Megan; Van Damme, Pierre; Limaye, Rupali; Vorsters, Alex (Frontiers in Public Health, 2023)
Cervical cancer due to human papillomavirus (HPV) infection is a leading cause of mortality among women in low-resource settings. Many Sub-Saharan African countries have introduced HPV vaccination programs at the national level in the last few years. However, countries are struggling to maintain sustainable coverage. This study focuses on the introduction and sustainability challenges, context-specific key lessons learned, and mechanisms of action to achieve high sustainable coverage from low and lower-middle-income countries (LLMICs) that have introduced HPV vaccination programs by collating evidence from a literature review and key informant interviews. Local data availability was a challenge across countries, with the lack or absence of registries, data collection and reporting mechanisms. Multi-sectoral coordination and early involvement of key stakeholders were cited as an integral part of HPV programs and facilitators for sustainable coverage. Key informants identified periodic sensitization and training as critical due to high staff turnover. Health workforce mobilization was fundamental to ensure that the health workforce is aware of the disease etiology, eligibility requirements, and can dispel misinformation. Schools were reported to be an ideal sustainable platform for vaccination. However, this required teachers to be trained, which was often not considered in the programs. District-level staff were often poorly informed and lacked the technical and logistic capacity to support vaccination rounds and data collection. To improve the sustainability of HPV vaccination programs, there is a need for timely microplanning, efficient preparedness assessment, assessing training approaches, periodic training, finding innovative ways to achieve equity and adoption of a bottom-up approach to ensure that processes between districts and central level are well-connected and resources are distributed efficiently.